OPTIMIZATION OF CHOLESTEROL ANALYSIS USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) - Pitaloka, Atika - (RC-INSTITUT, 2019)
Cholesterol levels in the blood can provide information about human?s health. This study aims to determine the optimum conditions of the HPLC instrumentation tool in cholesterol analysis and can determine cholesterol levels in the blood. The method used is the chromatographic method using HPLC. The mobile phase used in this study was methanol: water (65:35), and the stationary phase used CLC-Sil columns. Maximum wavelengthfor cholesterol was measured by UV-Vis spectrophotometer is 264 nm. The value of lineritas obtained R2 = 0.994, the system suitability test showed an area RSD value of 0.01797% and a retention time of 0.00102%. LDI 19.8015 (µg / mL) LOQcount 66.005 (µg / mL). Test for specificity at a retention time of 3.7 minutes. Measured cholesterol levels are 113.179 (mg / dl).